2017
DOI: 10.1007/s00167-017-4440-y
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient unicompartmental knee arthroplasty: who is afraid of outpatient surgery?

Abstract: PurposeIn recent years, duration of hospitalisation after knee arthroplasty has decreased and fast track and outpatient surgery protocols have been developed. Studies have shown that outpatient surgery is feasible, safe, and cost effective. However, the psychological well-being of patients undergoing outpatient surgery has never been described before. The purpose of this study was to investigate how patients experience outpatient surgery for unicompartmental knee arthroplasty (UKA), examining levels of anxiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 28 publications
1
38
0
Order By: Relevance
“… 2017 , Hoorntje et al. 2017 ). Fast-track TKR is not associated with higher readmission, reoperation, manipulations under anesthesia (MUA) or mortality rates (Husted et al.…”
mentioning
confidence: 99%
“… 2017 , Hoorntje et al. 2017 ). Fast-track TKR is not associated with higher readmission, reoperation, manipulations under anesthesia (MUA) or mortality rates (Husted et al.…”
mentioning
confidence: 99%
“…A welldesigned OTJA program provides safe surgical care with equivalent patient-reported outcomes, such as anxiety, depression, satisfaction, and pain, compared to standard "fast track patients" that require a 1-day hospitalization [30,31]. Furthermore, OTJA programs generate cost savings by improving OR efficiency via surgeon-specific instrumentation and online training tools and improving post-anesthesia care and pain control.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the results of Larson et al were found after TKA in an enhanced recovery pathway [11,20,21], data after outpatient surgery are lacking. Hoorntje et al [12] recently published their case-controlled study regarding the presence of symptoms of anxiety and depression, by means of the Hospital Anxiety and Depression Scale (HADS) in patients operated after UKA. They found that at the first postoperative day, the median HADS score was significantly (p=0.02) lower in the OS group compared to the ERP group and that patients in the OS group were significantly more satisfied (NRS satisfaction score, p=0.03) without any differences between both groups at 3-month follow-up [12] Pain relief and improved function are one of the principal aims of arthroplasty, thus it was expected that PROMs would improve significantly after knee arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…All disciplines should be informed about, and involved in the whole process. Together with well-defined patient-based selection criteria, a change in mind set and a multidisciplinary approach, OS pathways are as safe and efficient as conventional pathways, in terms of readmissions, complications [8,14] and clinical outcome [12,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation